Stok Rumput Laut Alami di Perairan Teluk Prigi Trenggalek Jawa-Timur - Achmad Kadi (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Wild seaweed is natural source in term of seed supply on aquaculture activity. In recent years, seaweed is the important aquaculture comodity from Indonesian provinces. Observation on wild seaweed in Prigi Bay, conducted in may 2011. The aim of the observation was to find out the condition and to measure the density of seaweed in Prigi Bay-Trenggalek East Java waters. Observation was carried out through survey method. Five observation stations were made the distance within the station was 1000 m parallel with the beach line, then divided in 100 m to become 10 applying points on each stations. Quadrat transect in located perpendicular from the beach line to slope area, 1x1m² frame placed on each 10 meter by Saito and Watanabe. Species biodiversity, density and dominancy were measure from raw data obtained and using the computing formula according Michael, Kusmana, Soerianegara and Indrawan. Three species were found: Chlorophytaceae and Phaeophytaceae. The total of wild seaweeds in density of observation site was 239,53 g/m² and Padina australis has the highest density among other ie 82,01 g/m² and dominant value of the species was 30,23 g/m². Seaweed which have economic value in observation site was Caulerpa, Halimeda, Padina and Sargassum.